Addiction to social networks and its relationship to the psychological feeling of adolescents - Deghriri, Ali bin Hamad bin Ahmed (Journal of Humanities & Social Sciences, 2017)
This research aimed at shed a flood of light on the relationship between addiction of social networks and the Depression, Social Anxiety, a Psychological Loneliness. The researcher has used the descriptive method since he studies the relationship between addiction of social networks and the Depression, Social Anxiety, a Psychological Loneliness. The research sample consisted of (343) High school and Intermediate level students from Samtah governorate. The results revealed that there is a positive correlational relationship with statistical significance between addiction of social networks on one hand and the Depression, Social Anxiety, a Psychological Loneliness on the other hand. The research results also showed (56%) of the sample were those who had moderate level of addiction whereas (%25.9) of the sample where those who had high level of addiction, and finally (% 18.1) of the sample where those who had low level of addiction (normal use). The research came up with a group of recommendations among which the most important one was spreading the awareness of the addiction risks of the social networks by media campaigns to urge the social networks’ users to use them wisely.